'Zbrodnia i kara' Fiodora Dostojewskiego w teatrze – przemiany gatunku (na przykładzie wybranych spektakli) - Gracla, Jadwiga (Załącznik Kulturoznawczy, 2021)
This text presents three performances, which are stage variants of Dostoevsky’s novel. The author shows and emphasizes the differences between the effect of the novel and the spectacle, indicates the consequences of eliminating fragments of the novel from the structure of the spectacle. It also shows the consequences of experts and formal entrants. The author pays particular attention to the problem of translating the text of the novel into the language of theater. He also points to the consequences of omitting the epilogue in some performances, which, in Dostoyevsky’s work, is an inseparable and most meaningful element. The directors omit this fragment in the presented productions, which leads to a change in the genre of the performance and changes the meaning of Dostoyevsky’s work. The musical show presented here should be considered a successful attempt to transfer it to the stage. The author also points to the experiments with the form of a novel in Polish theater, aimed at alternative history.